The Qur’anic Language in a Linguistic Perspective: The Language Engineering Viewpoint - Sa‘Adeddin, Mohammed Akram A.M. (Intellectual Discourse, 1994)
This article is an attempt to draw a plan for developing curricula for teaching the Qur’anic Language at the International Islamic University Malaysia (IIUM). The article is in four sections. The first offers an overview of Language Engineering, the language profile in Malaysia, the Qur ’anic Language teaching situation at IIUM, and the conditions for competent Corpus Planning. The second discusses the significance of the Qur’anic Language, and the Islamic semantic affinity between the Qur’anic Language and Bahasa Melayu. The third focuses on the implications of the Qur’anic language Corpus Planning for language teachers, materials writers and curriculum designers. The fourth briefly introduces our theory of interpretive reading, goes on to apply it to an active reading of sūratu likhlās, and considers the implications of this type of reading for the Qur’anic Language syllabus design.